Alab ng sining - Sy, Kristine Kaye T.
Alab ng Sining,a 17-minute video documentary, focuses on the performances by cultural artists and groups which tackle socio-political issues in picketlines, demonstrations, mobilizations, and State of the Nation Addresses or SONAs. The documentary features cultural artists and groups as they go about their goal of communicating effectively with their audience - the masses - who clamor for political, social, and economic changes and protest against any form of government suppression and/or oppression. The said cultural workers, the film maker believes, not only enlighten, educate, and entertain their audiences; above all, they aim to empower their audience and mirror their audience's sentiments regarding political, social, and economic issues. They know that they have a social responsibility towards the people and they take this social responsibility very seriously.